THE EFFECTIVENESS OF ENVIRONMENTALLY FRIENDLY ACCOUNTING AND PROFITABILITY IN MINIMIZING CORPORATE TAX LIABILITIES - Hetti Herawati; Ulfa Maesyaroh; Yogascitra Naufal (PT. Altin Riset Publishing, 2026)
This study aims to analyze the effect of green accounting and profitability on taxes payable in mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. Green accounting is measured through environmental performance based on PROPER, while profitability is measured using Return on Assets (ROA). The research sample consisted of 40 observations obtained using purposive sampling. The analysis was conducted using panel data regression with the Fixed Effect Model (FEM). The results showed that green accounting did not have a significant effect on taxes payable, while profitability had a significant negative effect. Simultaneously, green accounting and profitability have a significant effect on taxes payable with a coefficient of determination (R²) value of 0.864972. These findings indicate that companies with high profitability tend to engage in tax management, while the implementation of green accounting is more oriented towards social legitimacy than fiscal efficiency.